Comparitive Analysis between AHP & Fuzzy AHP: A Case Study on Flood Susceptibility of Koshi River Basin - Karki, Aashis Kumar; Chaudhary, Bipul; Khadka, Dikshya; Dahal, Pratiksha; Bajgain, Rupa; Shrestha, Reshma; Thapa, Ajay Kumar (Journal of Land Management and Geomatics Education, 2025)
The report compares the Analytical Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (FAHP) for flood susceptibility assessment in the Koshi Basin area. Both models are used in multi-criteria decision-making, but their effectiveness in handling complex environmental conditions varies. The study evaluates and compares the performance of these models in predicting flood-prone areas using the Area Under the Curve (AUC) of the Receiver Operating Characteristic (ROC) as a performance metric. The results show that the majority of the region falls under moderate flood risk, with low-risk zones accounting for 35.04% and 31.41% and high-risk areas covering 12.67% and 13.33%. The topographical wetness index was the most weighted criteria in both models, while aspect was the least affecting criteria. The AHP model showed good predictive capability with an AUC of 0.758, while the FAHP model demonstrated superior performance with an AUC of 0.802, attributed to its incorporation of fuzzy logic.